2019
DOI: 10.1016/j.jbankfin.2019.105610
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intraday dynamics and collateral selection in centrally cleared and bilateral repos

Abstract: Using a novel dataset, we study intraday trades of overnight general collateral repurchase agreements (repos) on Italian government bonds. We focus both on repos cleared by central counterparties (CCPs) and traded bilaterally. Intraday bond supply, liquidity and duration significantly affect the spread of repo rates over the European Central Bank (ECB) deposit rate, but after the ECB quantitative easing interventions this impact is much reduced. During the European sovereign debt crisis, the increase in margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Gürkaynak and Wright (2013) recommend using short windows around events to minimise the possibility that news unrelated to the event affects the outcomes of interest. The relative sparsity of overnight repo trades post h o,t -more than 70% of repo trades are concluded before the scheduled time of the OMO announcement-as well as the presence of strong intraday patterns in funding costs (Dufour, Marra, and Sangiorgi, 2019) hampers our ability to isolate the information effect in short windows around h o,t . Our empirical setting also makes it difficult to infer the long-run effects of information revealed by OMOs.…”
Section: Resultsmentioning
confidence: 99%
“…Gürkaynak and Wright (2013) recommend using short windows around events to minimise the possibility that news unrelated to the event affects the outcomes of interest. The relative sparsity of overnight repo trades post h o,t -more than 70% of repo trades are concluded before the scheduled time of the OMO announcement-as well as the presence of strong intraday patterns in funding costs (Dufour, Marra, and Sangiorgi, 2019) hampers our ability to isolate the information effect in short windows around h o,t . Our empirical setting also makes it difficult to infer the long-run effects of information revealed by OMOs.…”
Section: Resultsmentioning
confidence: 99%
“…1. Dufour et al (2019) and Boissel et al (2017) analyze the Italian repo market, which trades on MTS, and interestingly has both CCP clearing (in CC&G, clearing circa 80% of total daily notional of EUR 6.1 bn) and bilateral clearing (20%) in the morning of each trading day. On the basis of hourly data from 2010 to 2015 incorporating the European Sovereign Debt Crisis, they find that in relatively normal times repo spreads against the ECB deposit rate of trades centrally cleared, are lower than those cleared bilaterally.…”
Section: To Clear Centrally or Not To Clear Centrally?mentioning
confidence: 99%
“…The Italian repo market was studied by Dufour et al (2019) and Boissel et al (2017), who found that the CCP had lower counterparty risk. CCP repo spreads, on the other hand, surged more than bilateral repo spreads during the European sovereign debt crisis, reversing the situation.…”
Section: Central Clearing Counterpartiesmentioning
confidence: 99%